Pravni in praktični izzivi zaposlovanja tujcev - Franca, Valentina (Delavci in delodajalci, 2025)
Due to the shortage of workers, labor market migration in Central and Eastern Europe has intensified. Employing foreigners is a challenging process due to legal-administrative procedures and integration into the work environment, where linguistic, cultural, religious, and other differences are present. Foreigners often require additional training, which can cause tensions between local and foreign workers. The role of social partners in addressing these challenges remains weak. More attention needs to be paid not only to legislative changes but also to the development of migration policies for more effective integration of foreigners into the labor market and society.
Keywords: delodajalske organizacije; delovno dovoljenje; Delovno pravo; employers organizations; employment of foreing workers; integration into the labour process; migracije; sindikati; Slovenija; trade unions; tuji delavci; vključevanje v delovni proces; work permit; zaposlovanje tujcev